Folklorization of Stories about the Prophet Noah (S.A.V): Reasons and Solutions - Shukurova , Zilola; Mansurov, Sobir (International Journal of Psychosocial Rehabilitation, 2020)
Nosiriddin Rabguziy worked as a judge in Robotuguz in Khorazm (in the root of the khokim) in the XIV century. “Qisasi Rabguzi” is the unique work that has reached us and has been spread among people as “Kisasul-anbiyo.” This work, passed from mouth to mouth, has been creatively developed, added to, and completed by secretaries till recent years. And this is the cause why it has gone far from the original source, and this was the cause why it has undergone folklorization and has become very close to folklore stories.